Nerves and nerve injuries. Volume 1, - Tubbs, R. Shane; Rizk, Elias; Shoja, Mohammadali M. (Elsevier Science and Technology, 2015)
Nerves and Nerve Injuries is the first comprehensive work devoted to the nerves of the body. An indispensable work for anyone studying the nerves or treating patients with nerve injuries, these books will become the 'go to' resource in the field. The nerves are treated in a systematic manner, discussing details such as their anatomy (both macro- and microscopic), physiology, examination (physical and imaging), pathology, and clinical and surgical interventions. The authors contributing their expertise are international experts on the subject. The books cover topics from detailed nerve anatomy.- Resumé vydavatel